Membangun Spiritualitas Generasi Muda : Pendekatan Kontekstual dalam Pendidikan Agama Kristen - Michael Thobie; Nuvia Kurnia Sari; Andi Trio Suroso (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This article explores the importance of a contextual approach in Christian education for young people. By considering the cultural, social, and technological dynamics that influence the lives of young people today, this approach seeks to bridge the Christian faith tradition with modern realities. The research was conducted through a literature review and interviews with Christian educators, which showed that a contextual approach can strengthen spiritual connectedness and the relevance of Christian teachings in everyday life. This article offers practical guidance for educators in implementing this approach in the classroom.